Patients with high levels of circulating endothelial progenitor cells (EPC) following at least three months of anticoagulation for unprovoked venous thromboembolism (VTE) are at low risk of recurrent VTE—Results from the ExACT randomised controlled trial. - Bradbury, Charlotte (EClinicalMedicine, 2019)
BACKGROUND: There is clinical need for a laboratory biomarker to identify patients who, following an unprovoked venous thrombosis (VTE), are at low VTE recurrence risk and can discontinue anticoagulation after a limited treatment duration (3–6 m). This secondary analysis of the ExACT study aimed to evaluate whether quantitation of peripheral blood endothelial progenitor cells (EPCs) could improve prediction of VTE recurrence risk. METHODS: The ExACT study was a non-blinded, multicentre RCT comparing extended vs discontinued anticoagulation following a first unprovoked VTE. Adult patients were eligible if they had completed ≥3 months anticoagulation and remained anticoagulated. The primary outcome was time to first recurrent VTE from randomisation. Blood samples were taken at baseline and results correlated with clinical outcome over 2 years follow up. (Trial registration: ISRCTN:73819751 and EUDRACT:2101-022119-20) FINDINGS: 281 patients were recruited, randomised (between July 2011 and February 2015) and followed up for 24 months (Male:Female 2:1, mean age 63). Of these, 273 patients were included in the final analysis. Blood samples were received at baseline for Full Blood Count(n = 216), d-dimers(n = 205) and endothelial progenitor cell (EPC) quantitation by flow cytometry(n = 193). VTE recurrence was lower in the extended vs discontinued anticoagulation arms (5% vs 23%, HR 0.20(95%CI:0.09–0.46,p < 0.001)). Level of EPCs were lower in patients who later developed VTE recurrence (43.41 ± 7.69 cells/ml vs 87.1 ± 7.15 cells/ml, p = 0.02). Survival free from VTE recurrence was significantly improved in patients with EPCs ≥ 100 cells/ml vs EPCs < 100 cells/ml (HR 0.10(95%CI:0.01–0.75,p = 0.025)). INTERPRETATION: If confirmed, EPC quantitation may represent a novel biomarker that identifies patients at low VTE recurrence risk who are suitable for limited duration anticoagulation.